2019
DOI: 10.1111/cns.13181
|View full text |Cite
|
Sign up to set email alerts
|

Sema7A, a brain immune regulator, regulates seizure activity in PTZ‐kindled epileptic rats

Abstract: AimsSemaphorin7A (Sema7A) plays an important role in the immunoregulation of the brain. In our study, we aimed to investigate the expression patterns of Sema7A in epilepsy and further explore the roles of Sema7A in the regulation of seizure activity and the inflammatory response in PTZ‐kindled epileptic rats.MethodsFirst, we measured the Sema7A expression levels in patients with temporal lobe epilepsy (TLE) and in rats of a PTZ‐kindled epilepsy rat model. Second, to explore the role of Sema7A in the regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Our experiments showed changes in the number of bers crossing over the midline of the corpus callosum. [37,38]. The results of Golgi-Cox staining were evaluated by Sholl analysis by counting the number of intersections between concentric circles and dendrites to determine dendritic complexity and skeletonize dendritic spines to observe the number of changes [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments showed changes in the number of bers crossing over the midline of the corpus callosum. [37,38]. The results of Golgi-Cox staining were evaluated by Sholl analysis by counting the number of intersections between concentric circles and dendrites to determine dendritic complexity and skeletonize dendritic spines to observe the number of changes [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Kindling‐induced seizures are associated with activation of pro‐inflammatory pathways 40 and growth of mossy fibers, 41 which are known to contribute to epileptogenesis. However, the causal role of the DR 5‐HTergic neurons in kindling model of TLE is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified SEMA7A as a critical cue that restricts serotonergic innervation in the spinal cord [ 23 ]. In PTZ-kindled epileptic rats, Sema7A was upregulated in the epileptic brain and played a potential role in the regulation of seizure activity [ 24 ]. SEMA5A ( semaphorin 5A ), another gene of the semaphorin family, was identified to be an ASD-associated gene, and there was evidence of decreased expression of this gene in patients with autism [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%